Turnover Rate of NS3 Proteins Modulates Bluetongue Virus Replication Kinetics in a Host-Specific Manner - Ftaich, Najate (J Virol, 2015)
Bluetongue virus (BTV) is an arbovirus transmitted to livestock by midges of the Culicoides family and is the etiological agent of a hemorrhagic disease in sheep and other ruminants. In mammalian cells, BTV particles are released primarily by virus-induced cell lysis, while in insect cells they bud from the plasma membrane and establish a persistent infection. BTV possesses a ten-segmented double-stranded RNA genome, and NS3 proteins are encoded by segment 10 (Seg-10). The viral nonstructural protein 3 (NS3) plays a key role in mediating BTV egress as well as in impeding the in vitro synthesis of type I interferon in mammalian cells. In this study, we asked whether genetically distant NS3 proteins can alter BTV-host interactions. Using a reverse genetics approach, we showed that, depending on the NS3 considered, BTV replication kinetics varied in mammals but not in insects. In particular, one of the NS3 proteins analyzed harbored a proline at position 24 that leads to its rapid intracellular decay in ovine but not in Culicoides cells and to the attenuation of BTV virulence in a mouse model of disease. Overall, our data reveal that the genetic variability of Seg-10/NS3 differentially modulates BTV replication kinetics in a host-specific manner and highlight the role of the host-specific variation in NS3 protein turnover rate. IMPORTANCE BTV is the causative agent of a severe disease transmitted between ruminants by biting midges of Culicoides species. NS3, encoded by Seg-10 of the BTV genome, fulfills key roles in BTV infection. As Seg-10 sequences from various BTV strains display genetic variability, we assessed the impact of different Seg-10 and NS3 proteins on BTV infection and host interactions. In this study, we revealed that various Seg-10/NS3 proteins alter BTV replication kinetics in mammals but not in insects. Notably, we found that NS3 protein turnover may vary in ovine but not in Culicoides cells due to a single amino acid residue that, most likely, leads to rapid and host-dependent protein degradation. Overall, this study highlights that genetically distant BTV Seg-10/NS3 influence BTV biological properties in a host-specific manner and increases our understanding of how NS3 proteins contribute to the outcome of BTV infection.